Mechanical Behavior of Low Plasticity Clay Soil Stabilized with Rice Husk Ash - Jayo, B. (2022)
There is much research on how the addition of rice husk ash (RHA) and lime improves the mechanical behavior of the soil, particularly in clayey soils. RHA is a waste material and polluting for the environment; Therefore, its use can be considered as an economic and ecological alternative. The main objective of this analysis is to determine the influence of rice husk ash (RHA) to stabilize this type of soil. This research is based on the development of an alternative method for the improvement of low plasticity clay soils using an agricultural residue such as rice husk ash and lime for use in civil works. Soil mixtures with rice husk ash were made in different percentages to evaluate its geotechnical behavior as a stabilizer. Laboratory tests like OMC, MDD tend to increase when RHA is added. Shear strength increased as ash was added, where it reached a higher value with the addition of 40% RHA, increasing from 197.70 kPa to 323.00 kPa. Finally, the results obtained show an improvement due to the presence of RHA, however, the investigation is still in process to determine if the addition of higher RHA continues to improve or decrease its shear stress.